COMPLIANCE OF PREGNANT WOMEN CONSUMING IRON TABLETS TO ANEMIA EVENTS; A CROSS- SECTIONAL STUDY IN DARUL IMARAH ACEH BESAR DISTRICT - Nurbaiti Nurbaiti (Institute of Computer Science (IOCS), 2022)
The prevalence of anemia in pregnant women in Indonesia is still high. The main program to prevent anemia in pregnancy can be done by giving iron tablets to pregnant women, but this program is constrained by the low compliance of pregnant women to consume iron tablets. This study aims to determine the relationship between the adherence of pregnant women to consume iron tablets with the incidence of anemia. This design is cross-sectional. The research location is in Darul Imarah District, Aceh Besar. The research sample was 52 pregnant women in the third trimester of pregnancy. The sampling technique was carried out by consecutive sampling, namely all pregnant women entering the third trimester of pregnancy and meeting the inclusion and exclusion criteria were taken as samples until the required number of samples was met. Data analysis using ChiSquare test. The results showed that there was a relationship between adherence to consuming iron tablets and the incidence of anemia in pregnant women with a p-value of 0.000. In conclusion, adherence to taking iron tablets can increase hemoglobin levels so as to prevent the risk of anemia in pregnant women.